RISK AND PROTECTIVE FACTORS FOR DRUG USE AND PARTNER VIOLENCE AMONG WOMEN IN EMERGENCY CARE. Issue 5 (10th June 2013) - Gilbert, Louisa; El‐Bassel, Nabila; Chang, Mingway; Shaw, Stacey A.; Wu, Elwin; Roy, Lolita
<x xml:space="preserve">Abstract</x> This study estimates the effects of multilevel risk and protective factors on the co‐occurrence of drug use and intimate partner violence (IPV) victimization among a randomly selected sample of 241 women seeking emergency care in the Bronx, New York. Twenty percent of the sample reported both using drugs and experiencing IPV in the past 6 months. Multinomial logistic regression results indicate that childhood sexual abuse, incarceration history, psychological distress, binge drinking, partner drug use, and lower relationship decision‐making power are associated with both IPV victimization and drug use. The multilevel risk and protective factors associated with both IPV and drug use represent a combination of factors that are differentially associated with drug use only and with IPV victimization only outcomes. These findings suggest that women receiving emergency care who present both drug use and IPV are likely to need a greater range of services and more intensive interventions to address their cumulative risks.